Effect of Acid Treatment on the Recovery of Valuable Metals from Steel Plant Exhaust - Zeeshan A. Hameed; Junaid Saleem; Hira Lal; Ahsan Abdul Ghani; Muhammad Shoaib (Journal of Basic & Applied Sciences, 2016)
The response of different metals such as Zn, Fe, Pb, Cr and Mn during leaching of Electric Arc Furnace (EAF) dust in acid medium has been investigated. The major proportion of EAF dust constitutes of these metals and their recovery by means of a chemical process is not only economical but also imparts positive impact on the environment. The leaching of metals from dust is achieved using different concentration of sulphuric acid, and the dust samples have been characterized both before and after leaching. Based on the results, several recommendations have been suggested for the optimization of H2SO4 concentration,that lead to the maximum recovery of these metals. Under the optimized conditions, it has been determined that the satisfactory leaching yield of Zn (95%) can be obtained at a concentration of 1M.